Nephrectomy for renal tubular adenocarcinoma in feline: Case report - Maia Rocha, Cinthia; Estrela Dantas, Aline Vanessa (Pubvet, 2023)
Renal adenocarcinoma is a malignant tumor that affects tubular epithelial cells and is relatively rare in cats, typically occurring in the regions of the kidneys and bladder. Clinical symptoms are often nonspecific, making diagnosis challenging. Ultrasonography and exploratory laparotomy are essential diagnostic tools, but only histopathological examination confirms the presence of the disease. Treatment for renal neoplasms typically involves surgery and/or chemotherapy, aiming to improve the patient’s quality of life and survival. This case report describes a 12-year-old cat that presented uncontrollable vomiting. Abdominal ultrasonography revealed a neoformation in the right kidney, leading to an exploratory laparotomy and subsequent trans-surgical biopsy. Histopathological analysis confirmed the diagnosis of renal adenocarcinoma, leading to nephrectomy as treatment. The absence of metastases in surrounding tissues did not indicate the need for chemotherapy at that time. This report highlights the importance of using imaging tests and trans-surgical biopsy in the diagnosis and treatment of asymptomatic renal neoplasms.